(untitled) - Duong, Doan Trang (Can Tho, 2014)
The present research aims to investigate how CTU's english lectures and students perceive the EFL policies and pedagogical practices that are implemented at CTU
Keywords: English teachers,Tiếng Anh,Giáo viên tiếng Anh,English language; Training of,Dạy và học,Sự huấn luyện,Study and teaching